Patient enrollment per month (accrual) in clinical trials leading to the FDA approval of new cancer drugs - Michaeli, Daniel; Michaeli, Christoph T.; Albers, Sebastian; Michaeli, Julia (Targeted oncology, 2024)
Insufficient patient enrollment per month (=accrual) is the leading cause of cancer trial termination.
Online veröffentlicht: 31. Juli 2024
Gesehen am 28.10.2024